Endovascular thrombectomy without versus with different pre-intravenous thrombolysis in acute ischemic stroke: a network meta-analysis of randomized controlled trials - Guo, Sitong; Qin, Shiran; Tan, Sitao; Su, Henghai; Chen, Xiaoyu (Frontiers in Neurology, 2024)
Background The current guideline recommended the use of intravenous thrombolysis (IVT) before Endovascular thrombectomy (EVT), but the effectiveness and safety of tenecteplase compare to alteplase in patients before EVT remain uncertain. Methods We searched PubMed, Embase, Web of Science, and the Cochrane Library to identify eligible articles from inception until September 16, 2023. The primary outcome was functional independence (mRS 0–2) at 90 days. Secondary outcomes included excellent outcome (mRS 0–1) at 90 days, all-cause mortality at follow-up, successful reperfusion (TICI 2b–3) after the end of EVT, symptomatic intracranial hemorrhage (sICH) or any intracranial hemorrhage (aICH). The PROSPERO registration number is CRD42023470419. Results Eight randomized controlled trials (RCTs) were included involving 2,836 acute ischemic stroke (AIS) patients. Compared to EVT alone, tenecteplase (0.25 mg/kg and 0.4 mg/kg) + EVT and 0.9 mg/kg alteplase + EVT were significant difference associated with higher successful reperfusion (TICI 2b–3) after the end of EVT (RR = 2.31; 95% CI 1.15–4.63; RR = 2.31; 95% CI 1.00–5.33; RR = 1.05; 95% CI 1.01–1.09). And compared to 0.25 mg/kg tenecteplase + EVT, alteplase (0.6 mg/kg and 0.9 mg/kg) + EVT were significant difference associated with lower successful reperfusion (TICI 2b–3) after the end of EVT (RR = 0.45; 95% CI 0.22–0.90; RR = 0.45; 95% CI 0.23–0.91). The risk of aICH (RR = 1.50; 95% CI 1.07–2.09) was significantly higher for 0.6 mg/kg alteplase + EVT than EVT alone. There was no significant difference in functional independence (mRS 0–2), excellent outcome (mRS 0–1), all-cause mortality or sICH among the different IVT strategies (0.25 mg/kg or 0.4 mg/kg tenecteplase and 0.6 mg/kg or 0.9 mg/kg alteplase) before EVT. Conclusion The use of alteplase before EVT may potentially improve the successful reperfusion after EVT compared to tenecteplase. Due to the insufficient sample size, more high-quality RCTs are needed to confirm effectiveness and safety of tenecteplase compare to alteplase in patients before EVT. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: CRD42023470419.